Contemporary Logistics: Notion and Implementation - Braškienė, Liudmila (Ekonomika, 2003)
In this article the author has in view substantiating the universal character of the logistics concept and assessing opportunities of its wider implementation into practice. Most of the Lithuanian specialists currently comprehend the logistics as nothing but the economic process related to company’s operation spheres dealing with the delivery of goods or raw materials to the consumer (transportation, warehousing, inventories management, loads handling in warehouses, packaging etc.). As surveys revealed, business people most often admits that it is necessary to take into consideration the increasing number of interrelated factors when resolving the logistics problems and taking decisions within the permanently shrinking period of time. They still seldom rely on the integral concept, or “logistic way of thinking”, which enables to better understand the content of contemporary company’s operation, analyse the principal processes taking place within complex logistics systems and, especially important, manage the problems applying the integral approach in order to achieve the optimal results. The fact that this optimisation concept still is not “in demand” and there is no need for it may be determined not only by backwardness of economy and lagging behind of the global market development but also by still insufficient promoting of the up-to-date logistics approach and opportunities that it opens. Therefore, the author considers it is purposive to analyse the concept of the integrated logistics, which of late years dominates in the Western world economy, in order to reveal the formation basis and main principles, and present global practice examples of employing of the logistics concept thus highlighting the modem standpoint as concerns factors that determine the development and enhancement of logistics. In this paper, it is presented the etymological and logical analysis of the notion “logistics”, overview of the evolution of conceptual approaches of business logistics, and historical sequence of logistics paradigms. The retrospective analysis of the logistics concept revealed that in the course of development was empirically proved the objective character of its basic principles (employing the method of system analysis and the system method for logistics problems, rationality and aiming at optimal results when creating logistics systems, harmonisation of interests of all partners within the framework of logistics system and securing the synergy effect as a result of correct choice of priorities. That is precisely that makes it possible to employ the concept in different levels while ensuring the company’s local economic operation, its development and adaptation to the market conditions, and enhancing efficiency as well as optimising the whole social-economic system.